Perceived Performance, Intrinsic Motivation and Adherence in Athletes - Almagro, Bartolomé J. (Int J Environ Res Public Health, 2020)
Sports performance depends on a complex interaction of variables, such as psychological, physical, technical and tactical abilities. The purpose of the three studies described in this article was to validate an instrument to measure perceived performance in athletes (studies 1 and 2), and to analyze the predictive power of perceived performance, basic psychological needs and intrinsic motivation on the intention to be physically active (which was used as a predictor of adherence to sport) (study 3). In study 1, the Perceived Performance in Sports Questionnaire was validated in the Spanish sports context, analyzing its factorial structure, reliability, and temporal stability with 146 soccer players. The objective of study 2 was to check the factorial structure of the questionnaire with an objective performance measure (points scored and time played). The sample was 180 young basketball players. The objective of study 3 was to analyze the predictive power of basic psychological needs in exercise, intrinsic motivation, and perceived performance on the intention to be physically active in 339 athletes of fifteen different sports. The results show the reliability and validity of the questionnaire, and positive correlations with the points scored. Finally, the analysis of the structural equation model showed that the satisfaction of the need for competence predicted perceived performance and intrinsic motivation predicted perceived performance and intention to remain physically active.